Peril [compact disc, unabridged] - Woodward, Bob, 1943-; Costa, Robert, 1985- (Simon & Schuster, 2021)
The transition from President Donald J. Trump to President Joseph R. Biden Jr. stands as one of the most dangerous periods in American history. Woodward and Costa take readers deep inside the Trump White House, the Biden White House, the 2020 campaign, and the Pentagon and Congress, with vivid, eyewitness accounts of what really happened. They also provide a look at Biden's presidency as he faces the challenges of a lifetime: the continuing deadly pandemic and millions of Americans facing soul-crushing economic pain, all the while navigating a bitter and disabling partisan divide, a world rife with threats, and the hovering, dark shadow of the former president.